Pengaruh Kompetensi Manajerial Kepala Sekolah dan Profesionalitas Guru Terhadap Kinerja Guru di MTsN 16 Jombang - Azizah, Nurul; Ahdi, M Wafiyul; Hanifah, Hanifah (Universitas KH. A. Wahab Hasbullah, 2022)
This study aims to: (1) find out how the Principal's Managerial Competence at MTsN 16 Jombang (2) to know how the Professionalism of Teachers at MTsN 16 Jombang (3) to find out how Teacher Performance at MTsN 16 Jombang (4) how the influence of Principal Managerial Competence and Teacher Professionalism on Teacher Performance at MTsN 16 Jombang. This research is a quantitative study with a research sample of all teachers at MTsN 16 Jombang, totaling 36 teachers. Data collection techniques by observation, spread out questionnaires, documentation, and unstructured interviews. Data analysis used descriptive analysis, and multiple linear regression analysis using SPSS version 20.0 for Windows. The results showed: (1) The managerial competence of madrasah principals was in the high category with a percentage of 50% with an average of 110.05. (2) Teacher professionalism is in the medium category with a percentage of 36.1% with an average of 90.88. (3) Teacher performance in the high category with a percentage of 50% with an average of 111.08. (4) There is an effect of managerial competence of madrasah principals and teacher professionalism on teacher performance shown by a simultaneous significance test (F test) with the results of the Fcount value of 19.812 greater than Ftable 3.28 with a sig value of 0.000 less than 0.05 and the coefficient of determination. (R2) is 51.8% while the remaining 48.2% is explained by other variables that are not studied such as work motivation, work climate, and others.